Role of oxygen vacancies on light emission mechanisms in SrTiO3 induced by high-energy particles. (13th March 2017) - Crespillo, M L; Graham, J T; Agulló-López, F; Zhang, Y; Weber, W J
Abstract: Light emission under MeV hydrogen and oxygen ions in stoichiometric SrTiO3 are identified at temperatures of 100 K, 170 K and room-temperature. MeV ions predominately deposit their energies to electrons in SrTiO3 with energy densities orders of magnitude higher than from UV or x-ray sources but comparable to femtosecond lasers. The ionoluminescence (IL) spectra can be resolved into three main Gaussian bands at 2.0 eV, 2.5 eV and 2.8 eV, whose relative contributions strongly depend on irradiation temperature, electronic energy loss and irradiation fluence. Two main bands, observed at 2.5 eV and 2.8 eV, are intrinsic and associated with electron–hole recombination in the perfect SrTiO3 lattice. The 2.8 eV band is attributed to recombination of free (conduction) electrons with an in-gap level, possibly related to self-trapped holes. Self-trapped excitons (STEs) are considered suitable candidates for the 2.5 eV emission band, which implies a large energy relaxation in comparison to the intrinsic edge transition. The dynamics of electronic excitation, governs a rapid initial rise of the intensity; whereas, accumulated irradiation damage (competing non-radiative recombination channels) accounts for a subsequent intensity decrease. The previously invoked role of isolated oxygen vacancies for the blue luminescence (2.8 eV) does not appear consistent with the data. An increasing well-resolved band at 2.0 eV dominates at 170 K and below. It has been only previously observed in heavily strained and amorphous SrTiO3, and is, here, attributed to transitions from d ( t 2g ) conduction band levels to d ( e g ) levels below the gap. In accordance with ab initio theoretical calculations they are associated to trapped electron states in relaxed Ti 3+ centers at an oxygen vacancy within distorted TiO6 octahedra. The mechanism of defect evolution monitored during real-time IL experiments is presented. In conclusion, the light emission data confirm that IL is a useful tool to investigate lattice disorder in irradiated SrTiO3 .